CONTRIBUTION OF ARC MAGMATISM STUDIES IN EARLY STAGE MINERAL EXPLORATION - Udi Hartono (Jurnal Geologi dan Sumberdaya Mineral, 2009)
Indonesia contains at least 15 volcano-plutonic arcs with total length of approximately 9,000 km. The eight arcs contain known mineral deposits, while the rest may have mineral deposit prospects. The discovery of new mineral resources depends on research into the genesis of ore deposits and improved methods of finding them. In order to reduce a high exploration cost, knowledge of arc magma genesis is very important in mineral exploration before further study on mineral deposit genesis. Review on a number literatures suggests there is no linear correlation between potential porphyry-Cu/ epithermal mineralization and a single petrological/ geological factor. Mineral deposit formation is a product of interplay of magmatism, tectonics, volcanism, and fluid processes.Â Keywords : arc magma genesis, ore deposits, exploration